Genome-wide identification, characterization and expression analysis of the bZIP transcription factors in garlic (Allium sativum L.) - He, Shutao; Xu, Sen; He, Zhengjie; Hao, Xiaomeng (Frontiers in Plant Science, 2024)
The bZIP genes (bZIPs) play crucial roles in various biological processes, including development and stress responses. Although bZIPs have been thoroughly investigated in many plants, no comprehensive genome-wide analysis of bZIPs in garlic havehas been conducted. Here, 64 AsbZIP genes (AsbZIPs) were identified and classified into 10 subfamilies. We systematically analysedanalyzed the evolutionary characteristics of these AsbZIPs by investigating their chromosome location, gene structure, conserved motifs and gene duplication, revealingindicating crucial roles of gene replications in the expansion of AsbZIPs. Furthermore, the observed nucleotide diversity indicated a minor genetic bottleneck in AsbZIPs during domestication. Moreover, the identificationresult of cis-acting elements revealedindicated potential associations of AsbZIPs with garlic development, hormone and stress responses. Additionally, the expression profiles of AsbZIPs in diverse tissues and under various abiotic stresses and hormone treatments were analysedanalyzed viaby qRT-PCR, and several tissue-preferentially -expressed and stress/hormone-responsive AsbZIPs were identified. In additionaddition,Besides, Asa7G01972 and Asa7G01379 were differentially expresseddisplayed differential expression under various stresses and hormone treatmentshormone. Subsequent experiments, including yeast two-hybridization and yeast induction, validated their interactions with Asa1G01577, a homologue of ABI5, reinforcing their importance in the responsesignificance in responding to hormone and abiotic stresses. This study unveiled the characteristics of the AsbZIP superfamily and lays a solid foundations for further functional analysis of AsbZIPs in garlic.